Cardiovascular system, red blood cells, and oxygen transport in microgravity. (2016) - Gunga, Hanns-Christian; Ahlefeld, Victoria Weller von; Appell, Hans-Joachim, 1952-; (Flight physiologist), Werner, Andreas; (Of Deutsche Sporthochschule Köln), Hoffmann, Uwe
No abstract available